ECONOMIC-MATHEMATICAL MODELS OF INVESTMENT ACTIVITY IN HOUSING AND CONSTRUCTION SPHERE - E. Acri; I. Egorova (Вестник университета, 2018)
This study deals with to the creation of an economic and mathematical model of investment activity in housing construction. Given the emerging the market situation and the increasing pace of housing construction, it is necessary to create a model of investment activity in the housing and construction sector that will help to invest competently and take into account the interest of both the customer, the investor and the lender. Each of the parties in the investment cycle process has its own goals, objectives and risks, which must be taken into account with minimal costs. In the proposed economic-mathematical model, depending on the version of the task, factors such as loans for investment activities, additional costs for temporary resettlement of tenants of a reconstructed house, the probability of price risk associated with the sale of a renovated area in the housing market, etc., are taken into account. The model of a private investor investing his capital in the creation of a new housing stock also takes into account the compensatory principles in the relations between the investor-bodies of the city government.